Developing an integrated business model in the manufacturing industry – An AHP approach - G K L Chien; F T S Chan (Science in Information Technology Letters, 2021)
Due to the market competition in the current business environment, there are many pressures in the Small and Medium-sized Enterprise (SME) manufacturers. Most SMEs are facing challenges in the market change from Mass Production (MP) to Mass Customization (MC). The purpose of this study is mainly based on drilling down into an SME manufacturer, exploring the limitation in its current business model and determining the boundaries of its operation process. This research paper designs an Analytical Hierarchy Process (AHP) model to develop a new business model to resolve the MC issue in the SME manufacturers. The aims of the new business model should be to improve company profit. Thereby seven criteria in the AHP model are profit, Minimum Order Quantity (MOQ), flexibility, inventory control, delivery time, revenue from existing customers and revenue from new customers for customized products. The methodology is pilot-run the new business model and compares the results among the AHP, current and new business models. The results prove that the new business model not only solves the problems in MC but also create a synergic effect on the business. The study provides a method that uses an AHP model for developing an integrated business model for SME manufacturers.